Literature Review: Standardization of Rutin Compounds in Several Plant Types - Mierza, Vriezka; Odhia, Febry Nola; Tyasna, Putri Setya; Nisa, Dila Qhoirul; Andriani, Nadia (Jurnal EduHealth, 2022)
Rutin is a compound derived from flavonoids. Rutin is a quercetin glycoside with a disaccharide consisting of glucose and rhamnose. Rutin is known to have activity as an antioxidant, anti-radical, estrogenic, anti-inflammatory, antiviral, antitumor, cytotoxic and protects against organ damage. The manufacture of herbal medicines must first go through a standardization process. This review was conducted to identify the rutin contained in an extract by means of Visible Light, KLT, HPLC, and LCMS. This research uses the literature review method by collecting and identifying relevant research data sources or articles published online, through the Google Scholar web database and Science Direct.